2021
DOI: 10.1126/sciadv.abf0197
|View full text |Cite
|
Sign up to set email alerts
|

A CDC7 inhibitor sensitizes DNA-damaging chemotherapies by suppressing homologous recombination repair to delay DNA damage recovery

Abstract: Cell division cycle 7 (CDC7), a serine/threonine kinase, plays important roles in DNA replication. We developed a highly specific CDC7 inhibitor, TAK-931, as a clinical cancer therapeutic agent. This study aimed to identify the potential combination partners of TAK-931 for guiding its clinical development strategies. Unbiased high-throughput chemical screening revealed that the highest synergistic antiproliferative effects observed were the combinations of DNA-damaging agents with TAK-931. Functional phosphopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Next, we performed differential gene expression and gene set enrichment analysis (GSEA) on ERCC6L2 ‐deficient erythroid‐committed HSPCs to examine the molecular pathways impacted by ERCC6L2‐ silencing. In all, 21 genes were significantly upregulated in both patient and ERCC6L2 ‐KD cells (Figure 4C ; p adj < 0.05, fold change >1.5), including genes involved in DNA damage recovery (cell division cycle 7 [ CDC7 ], 12 epithelial cell transforming 2 [ ECT2 ] 13 ) and regulation of erythropoiesis (hemogen [ HEMGN ] 14 , 15 ). Moreover, hierarchical clustering of differentially expressed genes showed that patient and KD cells clustered most closely together (Figure 4D ), suggesting that ERCC6L2 ‐deficiency drives a specific biological signature.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we performed differential gene expression and gene set enrichment analysis (GSEA) on ERCC6L2 ‐deficient erythroid‐committed HSPCs to examine the molecular pathways impacted by ERCC6L2‐ silencing. In all, 21 genes were significantly upregulated in both patient and ERCC6L2 ‐KD cells (Figure 4C ; p adj < 0.05, fold change >1.5), including genes involved in DNA damage recovery (cell division cycle 7 [ CDC7 ], 12 epithelial cell transforming 2 [ ECT2 ] 13 ) and regulation of erythropoiesis (hemogen [ HEMGN ] 14 , 15 ). Moreover, hierarchical clustering of differentially expressed genes showed that patient and KD cells clustered most closely together (Figure 4D ), suggesting that ERCC6L2 ‐deficiency drives a specific biological signature.…”
Section: Resultsmentioning
confidence: 99%
“…Given the key role of CDC7 in the cell cycle and DNA synthesis [ 29 ], many inhibitors are being developed to serve as antitumor agents. Targeting CDC7 induces DNA replication stress and shows therapeutic effects when applied either alone [ 11 , 12 ] or in combination with other treatments [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the key role of CDC7 in the cell cycle and DNA synthesis [ 29 ], many inhibitors are being developed to serve as antitumor agents. Targeting CDC7 induces DNA replication stress and shows therapeutic effects when applied either alone [ 11 , 12 ] or in combination with other treatments [ 29 , 30 ]. Our results showed that a CDC7 inhibitor combined with chemotherapy can induce cell cycle arrest and apoptosis, but more evidence is needed to elucidate the mechanisms linking these two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesize that tumors with known origin activity alterations or a reliance on dormant origin usage are prime candidates for DDK + WEE1 inhibition. Work by others suggests that some types of pancreatic, esophageal, ovarian, and breast cancers may be vulnerable to DDKi (63), especially in combination with chemotherapeutic agents. This study did not look at potential synergy with Wee1i or utilize Ewing sarcoma models.…”
Section: Discussionmentioning
confidence: 99%